The Birmingham rehabilitation uptake maximisation study (BRUM): a randomised controlled trial comparing home-based with centre-based cardiac rehabilitation. Issue 1 (10th March 2008) - Jolly, K; Lip, G Y H; Taylor, R S; Raftery, J; Mant, J; Lane, D; Greenfield, S; Stevens, A
Abstract : Objective: To compare the outcomes of home-based (using the Heart Manual ) and centre-based cardiac rehabilitation programmes. Design: Randomised controlled trial and parallel economic evaluation. Setting: Predominantly inner-city, multi-ethnic population in the West Midlands, England. Patients: 525 patients referred to four hospitals for cardiac rehabilitation following myocardial infarction or coronary revascularisation. Interventions: A home-based cardiac rehabilitation programme compared with centre-based programmes. Main outcome measures: Smoking cessation, blood pressure (systolic blood pressure (SBP), diastolic blood pressure (DBP)), total cholesterol (TC) and high-density lipoprotein (HDL)-cholesterol, psychological status (HADS anxiety and depression) and exercise capacity (incremental shuttle walking test, ISWT) measured at 12 months. Health service resource use, quality of life utility and costs were quantified. Results: There were no significant differences in the main outcomes when the home-based was compared with the centre-based programme at 12 months. Adjusted mean difference (95% CI) for SBP was 1.94 mm Hg (−1.1 to 5.0); DBP 0.42 mm Hg (−1.25 to 2.1); TC 0.1 mmol/l (−0.05 to 0.24); HADS anxiety −0.02 (−0.69 to 0.65); HADS depression −0.35 (−0.95 to 0.25); distance on ISWT −21.5 m (−48.3 to 5.2). The relative risk of being a smoker in the home arm was 0.90. The cost per patient to the NHS was significantly higher in the home arm at £198, (95% CI 189 to 208) compared to £157 (95% CI 139 to 175) in the centre-based arm. However when the patients' cost of travel was included, these differences were no longer significant. Conclusions: A home-based cardiac rehabilitation programme does not produce inferior outcomes when compared to traditional centre-based programmes as provided in the United Kingdom.